A Tipping Point in Listening Effort: Effects of Linguistic Complexity and Age-Related Hearing Loss on Sentence Comprehension. (September 2018) - Ayasse, Nicole D.; Wingfield, Arthur
In recent years, there has been a growing interest in the relationship between effort and performance. Early formulations implied that, as the challenge of a task increases, individuals will exert more effort, with resultant maintenance of stable performance. We report an experiment in which normal-hearing young adults, normal-hearing older adults, and older adults with age-related mild-to-moderate hearing loss were tested for comprehension of recorded sentences that varied the comprehension challenge in two ways. First, sentences were constructed that expressed their meaning either with a simpler subject-relative syntactic structure or a more computationally demanding object-relative structure. Second, for each sentence type, an adjectival phrase was inserted that created either a short or long gap in the sentence between the agent performing an action and the action being performed. The measurement of pupil dilation as an index of processing effort showed effort to increase with task difficulty until a difficulty tipping point was reached. Beyond this point, the measurement of pupil size revealed a commitment of effort by the two groups of older adults who failed to keep pace with task demands as evidenced by reduced comprehension accuracy. We take these pupillometry data as revealing a complex relationship between task difficulty, effort, and performance that might not otherwise appear from task performance alone.